Modified methodology for determining the temperature profiles of inverted u-tubes steam generators used in pwr power plants (Brazilian Journal of Radiation Sciences, 2021)
The most common and reliable methodology for determining temperature profiles of Inverted U-tubes Steam Generators is using Computational Fluid Dynamics (CFD) programs. In this work, we developed a modified methodology, using the Wolfram Mathematica software, in order to determine, with good approximation, the temperature profiles of these kind of equipment. The first step was to determine expressions for the physical properties of the water in the operational conditions, like density, thermal conductivity, specific heat and dynamic viscosity. Geometrical parameters like tubes diameter and sub-channel flowing area, as well as the flow parameters like flow mass of primary and secondary fluid, were also considered for determining the numbers of Reynolds, Prandtl, Nusselt and, consequently, the variation of convective coefficients and the global heat transfer coefficient. With subroutines that use the method of the lines we were able to solve the partial differential equations applied to parallel and countercurrent heat exchangers with no phase change. The U-tubes SG were divided in two regions which the first one was calculated considering a parallel heat exchanger and the second one was calculated considering a countercurrent heat exchanger, depending on the flow direction of the primary and secondary circuit. During the phase change, a constant variation of the enthalpy was considered, making the primary fluid temperature decrease following a linear behavior. Using the developed methodology called “Enthalpy Ruler”, the encountered results were considered adequate, since the defined lengths are compatible with the constant variation of the enthalpy from the compressed liquid to saturated steam.